Size and Shape: The Influence of Packaging on South African BOP Consumers’ Decision-Making - Oodith, Pravina Devpersadh (Journal of Economics and Behavioral Studies, 2018)
The bottom of the pyramid (BOP) proposition espouses the use of ‘single-serve’ or ‘sachet’ packaging in order to enhance affordability, encourage consumption and offer an assortment of good-quality products to BOP consumers. This study assesses the influence of packaging (in relation to size and price of different quantities) on South African BOP consumers’ purchase decisions. The study analyses whether or not these consumers have a tendency to purchase smaller quantities of products as opposed to making bulk purchases. This study further investigates the impact that packaging criteria (storage, convenience of purchase, prices of different package sizes and reusability of packaging) have on consumers’ decision-making. The aim is to uncover South African BOP consumers’ perceptions of packaging as a decision-making influencer in order to formulate appropriate strategies that businesses can adopt in order to lucratively serve this market. Using area sampling, a sample of 600 BOP consumers living in relative poverty within the rural areas of South Africa was drawn. Data was collected using a self-developed questionnaire whose psychometric properties were statistically analyzed using descriptive and inferential statistics. The study’s results reveal that although South African BOP consumers view small quantities of products as convenient and easy to store, the majority have an inclination to purchase large quantities instead of smaller package sizes. South African BOP consumers are also enticed to purchase products that are packaged in reusable containers, thereby, enabling the containers to be re-used after the consumption of the contents. Practical recommendations are articulated for business organizations.